2014
DOI: 10.1162/jocn_a_00543
|View full text |Cite
|
Sign up to set email alerts
|

Processing Graded Feedback: Electrophysiological Correlates of Learning from Small and Large Errors

Abstract: Feedback processing is important for learning and therefore may affect the consolidation of skills. Considerable research demonstrates electrophysiological differences between correct and incorrect feedback, but how we learn from small versus large errors is usually overlooked. This study investigated electrophysiological differences when processing small or large error feedback during a time estimation task. Data from high-learners and low-learners were analyzed separately. In both high- and low-learners, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 71 publications
7
31
0
Order By: Relevance
“…Regardless, to our knowledge, this is the first study to report intrinsic motivation and augmented feedback processing, when considered together, predict a measure of motor learning. One other study showed evidence that intrinsic motivation predicted motor learning (Saemi et al, 2011), but this study did not consider augmented feedback processing; and two other studies showed evidence augmented feedback processing predicted motor learning (Luft et al, 2013(Luft et al, , 2014, but these studies did not consider intrinsic motivation. Interestingly, intrinsic motivation and augmented feedback processing were not significantly correlated, suggesting that individuals who are more intrinsically motivated to learn do not necessarily engage in greater augmented feedback processing while learning.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Regardless, to our knowledge, this is the first study to report intrinsic motivation and augmented feedback processing, when considered together, predict a measure of motor learning. One other study showed evidence that intrinsic motivation predicted motor learning (Saemi et al, 2011), but this study did not consider augmented feedback processing; and two other studies showed evidence augmented feedback processing predicted motor learning (Luft et al, 2013(Luft et al, , 2014, but these studies did not consider intrinsic motivation. Interestingly, intrinsic motivation and augmented feedback processing were not significantly correlated, suggesting that individuals who are more intrinsically motivated to learn do not necessarily engage in greater augmented feedback processing while learning.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, the difference in FRN amplitude is unlikely related to the degree of error represented by the feedback. This is because the Yoked group received feedback after trials with larger errors (although this difference only approached conventional significance [p = .09]), and feedback indicating larger errors elicits greater FRN amplitudes (Luft et al, 2014). Thus, if FRN amplitude was being driven by the degree of error represented by the feedback, then the Yoked group would exhibit a larger FRN amplitude.…”
Section: Frn Mean Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…According to the same logic, alpha suppression after feedback onset may be related to enhanced attention during feedback processing. Alpha oscillations are known to be suppressed by feedback presentation (Papo et al, 2007; Luft et al, 2014), although the effect is usually manifested during a later period of feedback processing. The difference in timing of the effect may be explained by the nature of the condensation task that demands greater attentional involvement in comparison with many behavioral tasks commonly used, thus leading to earlier attention-related alpha suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a similar pattern of enhanced beta power has been reported in the ventral striatum of animals during a reward-processing task (Berke, 2009; Courtemanche, Fujii, & Graybiel, 2003), it has been proposed that feedback-locked beta power represents reward-related signals from this region. Parietal feedback-locked beta power is reduced in humans following feedback during reward-learning tasks, such as the time estimation task (Luft, Nolte, et al, 2013; Luft, Takase, & Bhattacharya, 2013; van de Vijver et al, 2011). This reduction in feedback-locked beta power (desynchronization) is less pronounced when feedback indicates good performance, compared to bad performance.…”
Section: Introductionmentioning
confidence: 99%